Association of food habit with the COVID-19 severity and hospitalization: A cross-sectional study among the recovered individuals in Bangladesh. Issue 4 (December 2022) - Ganguli, Sumon; Howlader, Sabbir; Dey, Kamol; Barua, Suman; Islam, Md. Nazrul; Begum, Afroza; Sobahan, Md. Abdus; Chakraborty, Rivu Raj; Hawlader, Mohammad Delwer Hossain; Biswas, Paritosh Kumar
Background: It was assumed that dietary habits might influence the status of COVID-19 patients.Aim: We aimed at the identification of association of dietary habits with the COVID-19 severity and hospitalization.Methods: It was a retrospective cross-sectional study (n = 1025). We used bivariate and multivariate analyses to correlate the association between self-reported dietary patterns and COVID-19 severity and hospitalization.Results: Dietary habits (black tea, milked tea, pickles, black caraway seeds, honey, fish, fruits, vegetables, garlic, onion and turmeric) were identified with lower risk of COVID-19 severity and hospitalization. Interestingly, the consumption frequency (one-, two- or three-times/day) of rice - the staple food in Bangladesh - was not associated with COVID-19 severity and hospitalization for comorbid patients. In contrast, a moderate rice-eating habit (two times/day) was strongly associated with the lower risk of severity and hospitalization for non-comorbid patients. However, for both comorbid and non-comorbid patients, consumption of black tea, milked tea, pickles and honey were associated with a lower likelihood of severity and hospitalization. Overall, a high consumption (three-times/day) of fish, fruits and vegetables, a moderate consumption of garlic, onion and turmeric spices and a daily intake of black/milked tea, and honey were associated with reduced risk of COVID-19 severity and hospitalization.Conclusions: To reduce the severity of COVID-19, a habitual practice of intaking black tea, milked tea, black caraway seeds and honey along with dietary habit (rice, fish and vegetables) and with a moderate consumption of ginger, garlic, onion, mixed aromatic spices (cinnamon + cardamom + cloves) and turmeric might be suggested.